(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper contributes to the growing scholarship on internationalization of higher education, particularly in non-Western contexts. Literature in non-Western contexts highlights tensions around adopting approaches seen as ‘global standard’ where these reflect inequalities of power and prestige, shaped by coloniality. Drawing on conclusions from a policy document analysis (Al Furqani, forthcoming), this study is based on a thematic analysis of interviews with 10 academic staff members within one college. This study explored how academics and leaders conceptualised internationalisation, and how they related these conceptualisations to their pedagogical practices in courses, interpreting their responses through a decolonial frame. Faculty expressed positivity towards internationalization in general and commitment to specific aspects such as global employability and competence. However, they also identified tensions, such as the prioritization of English over Arabic, lower value being placed on local forms of knowledge, reliance on globalized curricula and materials, and so on. These speak to implicit understandings of latent coloniality in institutional approaches to internationalization in Oman. These findings have wider relevance to other Arab Gulf countries, as well as to other non-Anglophone countries in the process of internationalizing.